2015
DOI: 10.1038/ncomms9476
|View full text |Cite
|
Sign up to set email alerts
|

Purely organic electroluminescent material realizing 100% conversion from electricity to light

Abstract: Efficient organic light-emitting diodes have been developed using emitters containing rare metals, such as platinum and iridium complexes. However, there is an urgent need to develop emitters composed of more abundant materials. Here we show a thermally activated delayed fluorescence material for organic light-emitting diodes, which realizes both approximately 100% photoluminescence quantum yield and approximately 100% up-conversion of the triplet to singlet excited state. The material contains electron-donati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
652
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 898 publications
(671 citation statements)
references
References 48 publications
18
652
0
1
Order By: Relevance
“…35 They found that the PLQYs of the polymer neat films decreased with increasing Ir(ppy) 3 phosphor concentrations (0.5-29 mol.%), suggesting the presence of undesirable interchromophore interactions in the film when the phosphor content became more concentrated, which is consistent with the observations reported in the aforementioned studies. 27,29,31 Although the copolymer with 0.5 mol.% Ir(ppy) 3 phosphor exhibited the best PLQY of 81% among the series, a minimum of 3 mol.% phosphor was required to complete the energy transfer from the host to the dopant. Thanks to the bipolar characteristics of the host to facilitate both hole and electron injections and transport, a single-layered PLED [ITO/AQ1200/Poly(M6-MAco-Ir-2C-MA) ($30 nm)/LiQ (2 nm)/Al (100 nm)] was fabricated, where a 6 mol.% phosphor was found to show the best compromise between PLQY and charge transport in the polymeric emitting layer.…”
Section: Recent Advances In Non-conjugated Polymers For Pled Applicatsupporting
confidence: 81%
See 2 more Smart Citations
“…35 They found that the PLQYs of the polymer neat films decreased with increasing Ir(ppy) 3 phosphor concentrations (0.5-29 mol.%), suggesting the presence of undesirable interchromophore interactions in the film when the phosphor content became more concentrated, which is consistent with the observations reported in the aforementioned studies. 27,29,31 Although the copolymer with 0.5 mol.% Ir(ppy) 3 phosphor exhibited the best PLQY of 81% among the series, a minimum of 3 mol.% phosphor was required to complete the energy transfer from the host to the dopant. Thanks to the bipolar characteristics of the host to facilitate both hole and electron injections and transport, a single-layered PLED [ITO/AQ1200/Poly(M6-MAco-Ir-2C-MA) ($30 nm)/LiQ (2 nm)/Al (100 nm)] was fabricated, where a 6 mol.% phosphor was found to show the best compromise between PLQY and charge transport in the polymeric emitting layer.…”
Section: Recent Advances In Non-conjugated Polymers For Pled Applicatsupporting
confidence: 81%
“…Page et al very recently reported a library of random copolymers consisting of a carbazole-pyrimidine bipolar host and a pendant Ir(ppy) 3 phosphor for PLED applications (the best performing copolymer among the series, Poly(M6-MA-co-Ir-2C-MA), is shown in Fig. 9).…”
Section: Recent Advances In Non-conjugated Polymers For Pled Applicatmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, efficient reverse intersystem crossing (RISC) process and high fluorescence quantum yield ( Φ F ) are two essential requirements for efficient TADF emitters 1, 5. For the former one, an extremely small singlet‐triplet energy split (Δ E ST ) between lowest singlet excited state (S 1 ) and lowest triplet excited state (T 1 ) is highly desired to up‐convert triplet excitons to singlet excitons through thermal excitation 4, 6, 7, 8, 9, 10. Thus, electron‐donor (D)–electron‐acceptor (A) frameworks with a highly twisted way are generally employed to construct TADF emitters, as they can well isolate highest occupied molecular orbitals (HOMOs) in D moieties and lowest unoccupied molecular orbitals (LUMOs) in A moieties, respectively, resulting in small Δ E ST s and thus effective RISC process 11, 12, 13, 14, 15.…”
mentioning
confidence: 99%
“…Other than the compounds explained above, 5,10-bis(4-(4,6-diphenyl-1,3,5-triazin-2-yl)phenyl)-5,10-dihydrophenazine (DHPZ-2TRZ) was known [31], and the solution-processed 2,4,6-tris(4-(9 H-[9,3 :6 , 9 -tercarbazol]-9 -yl)phenyl)-1,3,5-triazine (G2TAZ), 2, 4,6-tris(4-(6 ,6 -di(9H-carbazol-9-yl)-9 H-[9,3 :9 ,3 : 6 ,9 :3 ,9 -quinquecarbazol]-9 -yl)phenyl)-1,3,5-triazine (G3TAZ), and G4TAZ emitters were also described [50]. In spite of the various design approaches, the EQE of the triazine compounds could not reach 20%, but the development of 9-(4-(4,6-diphenyl-1,3,5-triazin-2-yl)phenyl)-N3,N3,N6,N6-tetraphenyl-9H-carbazole-3,6-diamine (DACT-II) compound resolved the low EQE issue of the triazine compounds [51]. A diphenylaminocarbazole donor was the key to solving the problem by enabling 100% PLQY and 100% up-conversion efficiency with the help of the close to 0 eV E ST and the dipole orientation of the emitter.…”
Section: Triazine-modified Tadf Emittersmentioning
confidence: 99%